Deviation of Meanings with Homonymy as an Effort to Build Humor in Meme: A Semantic Study - Mochamad Ighfir Sukardi; Sumarlam Sumarlam; Sri Marmanto (Celt: A Journal of Culture, English Language Teaching & Literature, 2018)
The purpose of this study is (1) Describe how the use of homonymy for deviation of meaning as an effort to build humor in meme. (2) Describes a pattern of deviations of meaning that utilize homonymy in memes. This research is a descriptive-qualitative research. The data were collected using the method of simak and technique of notes. Data analysis in this research use method of match referential and connecting techniques to support codification, reduction, display, and interpretation in accordance with qualitative research framework. The results of this research, found the use of relations of homonymous meaning include the word base, derivative, foreign, and slang. Also found a deviation of meaning by utilizing homonymy that occurs due to euphemism, naming, and awarding pause. In addition to homonymy also found the use of homophony and then homography of word abbreviation. There are three patterns used to make deviations of meaning by utilizing homonymy. (1) The abused word is accompanied by text as explanatory. (2) The abused word is accompanied by the picture as explanatory.  (3) The abused word does not appear in the language symbol but the image with the text as explanatory. The holder of the important role of deviation of meaning in the meme is the image and the use of collocation. The right collocation is capable of tricking the reader before finally being startled by a second meaning. Collocation can determine the successful use of homonymy to build humor in a meme. If the meaning of collocation fails to deliver the reader to the meaning presented, then the meaning of the surprise fails to show.